Rational alcohol addiction: evidence from the Russian longitudinal monitoring survey - Badi H. Baltagi; Ingo Geishecker (Institute for the Study of Labor (IZA), 2006)
Alcohol consumption in Russia is legendary and has been reported to be the third leading cause of death in the former Soviet Union after heart disease and cancer. Are Russian alcohol consumers rational addicts? This paper uses eight rounds of a nationally representative Russian survey spanning the period 1994-2003 to estimate a rational addiction (RA) model for alcohol consumption. This is done in a panel data setting as well as on a wave by wave basis. The profile of the Russian drinker finds a huge difference between males and females and the model is estimated by gender. We do not find support for the RA model in Russia for women. For men, although we find that some implications of the RA model are satisfied, we fail to endorse the model empirically on grounds of implausible negative estimates of the discount rate.
Keywords: C23; D12; I10; 330; panel data; liquor consumption; rational addiction